Infant and child mortality in South Africa in the context of a high HIV prevalence : an investigation into changing mortality patterns at a fine age resolution - Brody, Linnea Lynn (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 98-111).